Power flow and loss tracing in deregulated transmission system using proportional tree method - Mohd. Herwan, Sulaiman; Mohd. Wazir, Mustafa; Omar, Aliman (Praise Worthy Prize S.r.l., 2011)
Link to publisher's homepage at http://www.praiseworthyprize.com/